Influence of dementia literacy and caregiving appraisal on the psychological wellbeing of informal caregivers of people with dementia: A cross-sectional study - Wang, Shanshan; Shan, Qiuju; Cheung, Daphne Sze Ki; Xu, Xinyi; Leung, Isaac Sze Him; Leung, Angela Yee Man (Frontiers in Medicine, 2022)
Background: Dementia informal caregiving is a global phenomenon. It is well documented that caregivers’ psychological health is often affected by busy caregiving schedules. Lawton’s two-factor model indicates that caregivers’ psychological well-being is influenced by caregiving appraisal and other caregiver factors. Our review also identified the significance of dementia literacy, which was an essential caregiver factor. However, it is imperative for a clear understanding of the mechanism of how psychological well-being is influenced by them. Objectives: To explore the association among dementia literacy, caregiving appraisal, and psychological well-being and the influencing mechanisms between them. Methods: Two hundred and twenty-three informal caregivers of people with dementia were involved in this cross-sectional study. Dementia literacy was measured by the Alzheimer’s Disease Knowledge Scale and Dementia Attitude Scale. Caregiving appraisal and psychological well-being were measured with the Caregiving Appraisal Scale and Ryff’s Psychological Well-being Scale, respectively. Descriptive statistics were used to describe the characteristics of participants and key outcome variables. Pearson’s correlation analysis was used to analyze the correlation among the variables. Structural equation modeling was used to examine the hypothetical mediating role of caregiving appraisal in the relationship between dementia literacy (i.e., knowledge of dementia and attitude toward dementia) and caregivers’ psychological well-being. Results: The hypotheses were partially confirmed. Attitude toward dementia was significantly associated with caregiving appraisal (r=.312, p<.01) and psychological well-being (r=.311, p<.01). However, knowledge of dementia was only significantly associated with psychological well-being (r=.136, p<.05). The structural equation modeling fitted well (p=.078, CFI=0.987, RMSEA=0.078). In the fitted model, caregiving appraisal partially mediated the association between attitude toward dementia and psychological well-being. In contrast, attitude toward dementia and caregiving appraisal fully mediated the association between knowledge of dementia and psychological well-being. Conclusion: Efforts can be exerted to improve dementia caregivers’ caregiving appraisal and attitude toward dementia to improve their psychological well-being.